Word order and information structure in Old Spanish - Ioanna Sitaridou (Universitat Autònoma de Barcelona, 2011)
In this article it is claimed that in Old Spanish the discourse-sensitive field is exclusively the preverbal one. Focusing on object preposing, it is shown that the object can: (i) either be linked to a topic reading (England 1980, 1983; Danford 2002); or (ii) an information focus reading (cf. Cruschina and Sitaridou 2011) –the latter only available as the rightmost element in Modern Spanish (cf. Zubizarreta 1998, inter alios); or (iii) a contrastive focus reading; or (iv) verum focus reading (cf. Leonetti & Escandell-Vidal 2009). Given all these different discourse readings which are linearized as verb second syntax, the testing hypothesis is that the verb second orders are an epiphenomenon of the organisation of information structure (cf. Wanner 1989; Bossong 2003; Sitaridou 2006, 2011 pace Fontana 1993; Cho 1997; Danford 2002; Fernández Ordóñez 2009; Molina 2010) rather than structural as in the Germanic languages.